Global Burden of Neurosurgical Disease. (1st September 2019) - Yacob, Alex; Carr, Christopher; Werner, Cassidy; Dumont, Aaron S
Abstract: INTRODUCTION: The Global Burden of Disease (GBD) is an international collaboration and the largest comprehensive investigation of global health disease burden ever conducted. Recently, we examined the shifting burden of neurosurgical disease in Vietnam and a handful of other nations. Our preliminary data supported the hypothesis that rapidly modernizing, middle-income nations have a particularly high burden of neurosurgical disease. To determine if this trend applied to middle-income nations at a global level, we extended our previous analysis to include all countries in the GBD database. METHODS: Using GBD data, we abstracted data for death by cause and prevalence of years lived with disability (YLD) for common neurosurgical pathologies for every nation in the world. Using data from the Global Health Data Exchange, we determined GDP per capita for each nation. We constructed histograms to visually correlate the global burden of neurosurgical disease with GDP per capita. RESULTS: A total of 16 of the 20 (80%) nations with the highest neurosurgical burden of disease were in the third income quartile, and 18 of the 20 (90%) nations with the highest burden of neurosurgical disease were in the middle 50% for YLD. In terms of deaths, 10 of the 20 (50%) nations were in the third quartile, and 16 of the 20 (80%) were in the middle 50%. CONCLUSION: The training of a neurosurgeon requires a considerable investment of resources, making it difficult to address any quickly growing neurosurgical disease burden. Middle-income nations have both fewer neurosurgeons per capita and a greater neurosurgical disease burden compared to wealthier nations. Furthermore, neurosurgical pathologies that disproportionately afflict middle-income nations amplify the deleterious effects of any shortage of neurosurgeons. This trend is concerning, and suggests a need for greater international cooperation, focus, and investment in developing neurosurgical resources in middle-income and developing nations.